DETERMINAN KEJADIAN IKTERUS NEONATORUM DI RS MUHAMMADIYAH SELOGIRI WONOGIRI - Ramadhany, Nurul Fajar; widodo, pratikto; soleman, sanirahman (Fakultas Kedokteran Universitas Islam Al-Azhar, 2020)
Background . Neonatal jaundice is a clinical condition in infants characterized by jaundice staining on the skin and sclera due to excessive conjugated bilirubin buildup . This study aims to know the determinants of neonatal jaundice, include sex, type of birth, length of stay after birth, stimulation of early breastfeeding, formula feeding, fever after birth, amniotic color, birth weight, birth length, weight loss, gestational age, and APGAR scores at Muhammadiyah Selogiri Hospital, Wonogiri. Method. This is a case control research using total sampling . Case criteria in this study were patients with a diagnosis of neonatal jaundice and control criteria who were not jaundice . The data were analyzed by chi square and analysis of multivariate with logistic regression. Result. Based on multivariate analysis, length of stay (p value: 0.001; OR: 4.582), Early Initiation of Breastfeeding (p value: 0.002; OR: 5.146), Formula feeding (p value: 0.000; OR: 0.319), birth weight ( p value: 0,000; OR: 35,352), Body length (p value: 0.047; OR: 0.499), Weight loss (p value: 0,000; OR: 2.795), Apgar score (p value: 0,000; OR: 0.030) . Based on logistic regression analysis non-vaginal delivery (p value: 0.027; aOR: 7.372), normal body weight (p value: 0.000; aOR: 122.372 ), no asphyxia (p value: 0,000; aOR: 227,589 ). Conclusion Infants who was born by non-vaginal delivery have risk of 7.372 times compared to vaginal delivery infants. Babies who were discharged < 3 days had a risk of 4.582 times greater. Early Initiation of Breastfeeding stimulation related to exclusive breastfeeding has a 5.146 times relationship to the incidence of Jaundice Breastmilk and Breastfeeding Jaundice jaundice . Normal infant weight is at a risk of 35,352 times related to the length of treatment after birth and the incidence of normal Jaundice. Weight loss in newborns is 2.795 times the risk of experiencing Breastmilk Jaundice and normal Jaundice.